2017
DOI: 10.1016/j.peptides.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoids counterbalance the synergism between endothelin-1 and angiotensin II in mesenteric veins of trained rats

Abstract: Exercise-induced adaptations of the modulating mechanisms that influence the angiotensin (Ang II) responses assume different features depending on the venous bed. In femoral veins, exercise mobilizes vasodilator prostanoids to cooperate with NO in order to maintain reduced Ang II responses. On the other hand, exercise's influence on the Ang II responses in veins that drain blood from the mesenteric region has been poorly described. Therefore, the present study aimed to identify the effects of a single bout of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These adaptations generally involve improved endothelial function (de Moraes, Davel, Rossoni, Antunes, & Zanesco, 2008; Guizoni et al., 2016; Husain et al., 2006). Other studies found that the actions of the effector peptides of RAAS on blood vessels can also be modulated as a consequence of exercise (Chies et al., 2003, 2017; Maeda, Iemitsu, Jesmin, & Miyauchi, 2005; Park et al., 2012). Nevertheless, studies examining the effects of exercise on Ang II‐induced vasoconstriction in aortas of 2K1C animals are scarce in the literature, although this is one of the most used experimental models employed to evaluate the endothelial mechanisms that modulate vascular tonus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These adaptations generally involve improved endothelial function (de Moraes, Davel, Rossoni, Antunes, & Zanesco, 2008; Guizoni et al., 2016; Husain et al., 2006). Other studies found that the actions of the effector peptides of RAAS on blood vessels can also be modulated as a consequence of exercise (Chies et al., 2003, 2017; Maeda, Iemitsu, Jesmin, & Miyauchi, 2005; Park et al., 2012). Nevertheless, studies examining the effects of exercise on Ang II‐induced vasoconstriction in aortas of 2K1C animals are scarce in the literature, although this is one of the most used experimental models employed to evaluate the endothelial mechanisms that modulate vascular tonus.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ang II‐induced vasoconstriction is strictly modulated by endothelium‐derived mediators. Nitric oxide (NO), prostanoids and hyperpolarizing substances produced by the endothelium may act in isolation or in combination to modulate the vascular responses to Ang II (Chies et al., 2017; Chies, Rossignoli, Baptista, de Lábio, & Payão, 2013; da Silva, de Souza Rossignoli, Carrillo‐Sepúlveda, Barreto‐Chaves, & Chies, 2011; Tirapelli et al., 2005). Thus, modifications in the endothelial functioning, accompanied or not by changes in the smooth muscle cells or the extracellular matrix, may lead to hypertension and/or contribute to its maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation